2020
DOI: 10.1093/jnci/djaa122
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Use Disorder and Overdose in Older Adults With Breast, Colorectal, or Prostate Cancer

Abstract: Background Despite high rates of opioid therapy, evidence about the risk of preventable opioid harms among cancer survivors is underdeveloped. Our objective was to estimate the odds of opioid use disorder (OUD) and overdose following breast, colorectal, or prostate cancer diagnosis among Medicare beneficiaries. Methods We conducted a retrospective cohort study using 2007-2014 SEER-Medicare data for cancer survivors with a fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…Medicaid insurance and tumor type were significantly associated with higher odds of new persistent opioid use, as were Ewing sarcoma and osteosarcoma. Our study confirms the previously published finding that opioid use after cancer treatment warrants attention 15,16 . Our study is novel in that it provides a close examination of new persistent use in AYAs, a unique patient population diagnosed with cancer at the outset of their adult lives.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Medicaid insurance and tumor type were significantly associated with higher odds of new persistent opioid use, as were Ewing sarcoma and osteosarcoma. Our study confirms the previously published finding that opioid use after cancer treatment warrants attention 15,16 . Our study is novel in that it provides a close examination of new persistent use in AYAs, a unique patient population diagnosed with cancer at the outset of their adult lives.…”
Section: Discussionsupporting
confidence: 89%
“…Recent studies have indicated that as many as 17% of older adults with cancer are at risk of becoming new persistent opioid users; this is commonly defined as receiving 2 or more opioid prescriptions after the completion of therapy 13,14 . In these studies, identified risk factors for new persistent use include surgery, a prior MH diagnosis, concomitant use of sedative‐hypnotics (eg, lorazepam), and noncommercial insurance 13‐17 . Whether these associations are observed in AYAs has not been evaluated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 CRC, in particular, has been associated with a remarkably heightened risk of opioid overdose. 14 Managing pain among this population while minimizing the risk of opioid dependence or overdose thus presents a significant challenge. Nevertheless, despite the risk of overdose, patients in our study who received opioids for 90 consecutive days before admission demonstrated significantly decreased inpatient mortality as compared with short term and nonopioid users.…”
Section: Discussionmentioning
confidence: 99%
“…Third, our study design required that we exclude individuals who died within 24 months of cancer diagnosis. This includes individuals who may have experienced disease regression and died from their cancer and those who died of an opioid overdose [a rare event ( 35 )]. Fourth, it is unclear whether our results generalize to other states.…”
Section: Discussionmentioning
confidence: 99%